Estimating the shadow economy at the provincial level in Indonesia: A MIMIC model approach - Lukman, Raif Maulana; Kartiasih, Fitri (Jurnal Ikatan Sarjana Ekonomi Indonesia, 2025)
The shadow economy encompasses economic activities that are not recorded in the Gross Domestic Product (GDP), resulting in reporting bias and diminished state revenue. This study estimates the size of the shadow economy across 34 Indonesian provinces from 2015 to 2021 using the Multiple Indicators and Multiple Causes (MIMIC) method. The results indicate that the estimated average shadow economy ranges from 4.73% to 42.64% of the provincial GRDP. Key influencing factors include tax burden, government regulations, regional autonomy, self-employed labor, and economic openness. These findings support policies aimed at reducing the shadow economy through tax efficiency, improved regulations, and enhanced welfare for micro, small, and medium enterprises (MSMEs) backed by local governments. Keywords: shadow economy; MIMIC model; regulation; tax burden JEL Classification: E61; E62